DEVELOPMENT OF A THEMATIC ARABIC LANGUAGE MODULE BASED ON LOCAL WISDOM AT DAYAH DARUL FITIYAN BANDA ACEH - Zikrullah Nuzuli (Al-Mubin, 2025)
This study aims to develop a thematic Arabic language learning module based on local wisdom at Dayah Darul Fitiyan Banda Aceh. The background of this study is the need for integration of local culture in Arabic language learning so that the material is more contextual, interesting, and relevant to the lives of santri. This study employs the Research and Development (R&D) model proposed by Borg and Gall. The results of the development indicate that the locally-based thematic module can enhance students' interest in learning and their understanding of Arabic language material. Validation by subject matter experts and language experts confirms that the module is highly suitable for use. Thus, the integration of local values into Arabic language material has proven to strengthen the meaning and application of the language in daily life.